2022
DOI: 10.1136/ard-2022-223469
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD14+ monocyte-derived oxidised mitochondrial DNA in the inflammatory interferon type 1 signature in juvenile dermatomyositis

Abstract: ObjectivesTo define the host mechanisms contributing to the pathological interferon (IFN) type 1 signature in Juvenile dermatomyositis (JDM).MethodsRNA-sequencing was performed on CD4+, CD8+, CD14+and CD19+cells sorted from pretreatment and on-treatment JDM (pretreatment n=10, on-treatment n=11) and age/sex-matched child healthy-control (CHC n=4) peripheral blood mononuclear cell (PBMC). Mitochondrial morphology and superoxide were assessed by fluorescence microscopy, cellular metabolism by13C glucose uptake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Immune complexes involving ribonucleoprotein are potent induces of mitochondrial ROS and superoxide,32 leading to loss of mitochondrial membrane potential and extrusion of oxidised mitochondrial DNA (mtDNA)33 where it is a component of low-density granulocytes NETosis in SLE 32. mtDNA is a potent inducer of IFN-I via TLR934 and cGAS-STING 35 36. Chronic IFN exposure has been implicated driving downregulation of mitochondrial metabolism in SLE T-cells, through NAD+depletion, leading to reduced viability and greater cell death following TCR stimulation 37.…”
Section: Discussionmentioning
confidence: 99%
“…Immune complexes involving ribonucleoprotein are potent induces of mitochondrial ROS and superoxide,32 leading to loss of mitochondrial membrane potential and extrusion of oxidised mitochondrial DNA (mtDNA)33 where it is a component of low-density granulocytes NETosis in SLE 32. mtDNA is a potent inducer of IFN-I via TLR934 and cGAS-STING 35 36. Chronic IFN exposure has been implicated driving downregulation of mitochondrial metabolism in SLE T-cells, through NAD+depletion, leading to reduced viability and greater cell death following TCR stimulation 37.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested dysregulated mitochondrial gene expression as an inciting factor in the upregulation of the IFN pathway [32]. Further study is needed on the hypothesis that the innate immune system inappropriately recognizes mitochondrial DNA as immunogenic, triggering a proinflammatory response that then drives the IFN type 1 pathway [33].…”
Section: The Type 1 Interferon Pathwaymentioning
confidence: 99%
“…In one of these studies, NETs were shown to contain mitochondrial DNA (mtDNA) 117 , which is notable as studies in SLE have shown that mitochondrial dysfunction leads to the extrusion of oxidized mtDNA in NETs, which in turn induces an type I interferon response 119 . Indeed, gene expression network analysis of muscle has implicated a role for mitochondrial dysfunction in JDM, and a recent study demonstrated that abnormal mitochondrial function in monocytes (including the presence of enlarged mitochondrial networks or ‘megamitochondria’) in patients with JDM leads to the production of oxidized mitochondrial DNA and drives further type I interferon production 120 , 121 . Furthermore, anti-mitochondrial autoantibodies are present in the serum of some patients (1% (4/371) of patients in one enzyme-linked immunosorbent assay (ELISA)-based analysis) 122 .…”
Section: Pathophysiologymentioning
confidence: 99%